The Influence of Financial Literacy, Risk Tolerance, and Investment Planning on the Accumulation of Capital in Indonesian Middle Class - Helvianto, Ahmad Wimbo; Madyanti, Aniza Nur (West Science Interdisciplinary Studies, 2024)
This research examines the influence of financial literacy, risk tolerance, and investment planning on capital accumulation in middle-class households in Indonesia. Using a quantitative research design, data from 130 respondents were collected through a structured questionnaire and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results show that financial literacy, risk tolerance, and investment planning significantly contribute to wealth accumulation. Besides, risk tolerance partially mediates the effects of financial literacy, wealth accumulation, investment planning, and wealth accumulation. These findings underlined the importance of financial knowledge, strategic planning, and balanced risk-taking in the formation of financial well-being. The findings carry an important message for policymakers, financial institutions, and households in the design of relevant financial education programs and specific investment strategies.
Keywords: Financial Literacy; Risk Tolerance; Investment Planning; Wealth Accumulation; Middle-Class Households